2005
DOI: 10.1021/jf050539m
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Phytosterol Oxides in Enriched and Nonenriched Spreads:  Application of a Thin-Layer Chromatography−Gas Chromatography Methodology

Abstract: The content of phytosterol oxidation products (POPs) in enriched and nonenriched commercial spreads was evaluated by thin-layer chromatography-gas chromatography (TLC-GC). Oxides of -sitosterol, campesterol, and stigmasterol were produced by thermo-oxidation (7-hydroxy, 7-keto, and epoxy derivatives) and chemical synthesis (triol derivatives), which were then separated and identified by TLC-GC. Their identification was further confirmed by GC-mass spectrometry (GC-MS). The total amounts of phytosterols found w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 33 publications
3
49
0
Order By: Relevance
“…Soupas et al (39), analyzing the oxidative stability of phytosterols in nonfat heat-treated milk enriched with 0.5% phytosteryl esters during its storage in different conditions (room temperature and 4°C), found values between 203 and 131 µg of oxidized POPs/100 g of milk. In previous works with phytosterol-enriched spreads, values around 105.7 µg/g of fat were obtained (25). Other papers showed no (40) or only a small formation of COPs (41) in milk heated under pasteurization or ultrahigh-temperature conditions.…”
Section: Resultsmentioning
confidence: 95%
“…Soupas et al (39), analyzing the oxidative stability of phytosterols in nonfat heat-treated milk enriched with 0.5% phytosteryl esters during its storage in different conditions (room temperature and 4°C), found values between 203 and 131 µg of oxidized POPs/100 g of milk. In previous works with phytosterol-enriched spreads, values around 105.7 µg/g of fat were obtained (25). Other papers showed no (40) or only a small formation of COPs (41) in milk heated under pasteurization or ultrahigh-temperature conditions.…”
Section: Resultsmentioning
confidence: 95%
“…This oxidative behaviour agrees with what has already been observed in previous studies of COP (Zunin et al 1998), where the 7-keto derivative was pointed out as a tracer of the oxidation process. In addition, 7-keto derivative was the major POP in emulsified spreads (Conchillo et al 2005). Thus, it was concluded that 7-keto derivatives represent a simple, reliable marker of the extent of PS oxidation in food (Cercaci et al 2007).…”
Section: Impact Of Frying On the Total Amount Of Psmentioning
confidence: 95%
“…Similar results were obtained in other studies (Conchillo et al, 2005b;Valencia et al, 2008), showing that the lack of oxygen in the modified atmosphere packaging is greater than in the vacuum one, and therefore the protection of food samples from oxidation is superior. Also, cooked samples stored under frozen conditions were found to suffer more oxidation processes than raw ones (Conchillo et al, 2005a), demonstrating that cooking promotes cholesterol oxidation during storage.…”
Section: B) Storagementioning
confidence: 99%
“…This is one of the reasons why many phytosterol-enriched foods have been commercialised since 1995, when the first enriched fat yellow spread was launched. With the inclusion of these enriched foods in the diets, the dietary intake of phytosterols increases (Conchillo et al, 2005a;Kuhlmann et al, 2005).…”
Section: Introductionmentioning
confidence: 99%